LaTiOxNy Thin Film Model Systems for Photocatalytic Water Splitting: Physicochemical Evolution of the Solid–Liquid Interface and the Role of the Crystallographic Orientation. (31st March 2017) - Pichler, Markus; Si, Wenping; Haydous, Fatima; Téllez, Helena; Druce, John; Fabbri, Emiliana; Kazzi, Mario El; Döbeli, Max; Ninova, Silviya; Aschauer, Ulrich; Wokaun, Alexander; Pergolesi, Daniele; et al.
Abstract : The size of the band gap and the energy position of the band edges make several oxynitride semiconductors promising candidates for efficient hydrogen and oxygen production under solar light illumination. Intense research efforts dedicated to oxynitride materials have unveiled the majority of their most important properties. However, two crucial aspects have received much less attention: One is the critical issue of compositional/structural surface modifications that occur during operation and how these affect photoelectrochemical performance. The second concerns the relation between electrochemical response and the crystallographic surface orientation of the oxynitride semiconductor. These are indeed topics of fundamental importance, since it is exactly at the surface where the visible‐light‐driven electrochemical reaction takes place. In contrast to conventional powder samples, thin films represent the best model system for these investigations. This study reviews current state‐of‐the‐art oxynitride thin film fabrication and characterization, before focusing on LaTiO2 N, selected as a representative photocatalyst. An investigation of the initial physicochemical evolution of the surface is reported. Then, it is shown that after stabilization the absorbed photon‐to‐current conversion efficiency of epitaxial thin films can differ by about 50% for different crystallographic surface orientations, and be up to 5 times larger than for polycrystalline samples. Abstract : Oxynitride photoanode thin film heterostructures for solar water splitting based on LaTiO x N y are fabricated. Polycrystalline samples are used to probe surface physicochemical evolution induced by photoelectrochemical tests. A comparative analysis of samples with different crystalline properties shows that not only the crystalline quality, but also the crystallographic surface orientation determines the photoelectrochemical response.